Pengaruh Edukasi Melalui Media Leaflet Terhadap Pengetahuan Keluarga Tentang Perawatan Pasien Gangguan Jiwa - Halimah, Nor; Sholikhah, Siti; Saifudin, Moh. (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Mental health refers to a condition in which an individual is able to develop physically, mentally, spiritually, and socially, thereby becoming aware of their own capabilities, managing stress effectively, working productively, and contributing meaningfully to their community. This study aimed to analyze the effect of leaflet-based education on family knowledge regarding the care of patients with mental disorders in Turi Subdistrict, Lamongan Regency. A pre-experimental design with a one-group pre-test and post-test approach was employed. The population consisted of 93 families. Data were collected using a structured closed-ended questionnaire and analyzed using the Wilcoxon Signed-Rank Test with a significance level of p < 0.05. The results showed that prior to the intervention, nearly 59.1% of the families had low levels of knowledge. Following the intervention, more than 44.1% demonstrated good knowledge. Statistical analysis yielded a significance value of p = 0.000 and a Z-score of -6.363, indicating a significant effect of leaflet-based education on family knowledge regarding mental health care. Educational interventions such as leaflets may serve as an effective strategy to improve family knowledge and address mental health literacy gaps.